Prolonged preoperative hospital stay is a risk factor for complications after emergency colectomy for severe colitis. (November 2013) - Bartels, S. A. L.; Gardenbroek, T. J.; Bos, L.; Ponsioen, C. Y.; D'Haens, G. R. A. M.; Tanis, P. J.; Buskens, C. J.; Bemelman, W. A.
Abstract Aim Risk factors for postoperative complications in patients undergoing emergency colectomy for severe colitis in inflammatory bowel disease have hardly been studied. Therefore, this study aimed to define predictors of a complicated postoperative course in these patients. Method A retrospective review was performed of 71 consecutive patients who underwent emergency colectomy for severe colitis between 1999 and 2012 at a tertiary referral centre. Complications were graded according to the Clavien–Dindo classification. Patients with a complication Grade II or higher were compared with those with no complications or a Grade I complication. Results Nineteen patients (26.7%) had at least one postoperative complication classified as Clavien–Dindo Grade II or higher. In the group with postoperative complications, patients had a higher age (mean 45 vs 35 years, P = 0.020) and a higher body mass index (BMI) (mean 25.9 vs 21.0 kg/m2, P = 0.006). Length of preoperative hospital stay (median 15 vs 6 days, P = 0.032) was longer in the group with postoperative complications. During the study period, the preoperative hospital stay decreased by 0.8 days per study year (95% CI 0.2–1.5 days, P < 0.001). This did not influence the complication rate over time, however. Conclusion Factors increasing the risk of complications after emergency colectomy for severe colitis were a higher age, a higher BMI and a longer preoperative hospital stay.